A SYNTACTIC ANALYSIS ON NEGATIVE MARKERS OF ‘NO’ AND ‘NOT’ FOUND IN THE JAKARTA POST JUNE 2013 EDITION - MUTHMAINNAH, SYARIFAH (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Syntax, Negation, Negative Markers, Category, Distribution, Function, The Jakarta Post. In communication, people usually deliver information, agreement, denial or negation, and many more. The concept of negation is universal or exists in every language in the world. Negation is the contradiction or denial of something. The writer chose the negat ive markers ‘no’ and ‘not’ as the object in discussing the negation in this research. They are just like having the same distribution and conveying the similar meaning in negation. Therefore, this study was done to answer the problems of the research, namely: (1) What are the categories of ‘no’ and ‘not’ based on their distribution in phrase found in The Jakarta Post June 2013; (2) What are thecategories of ‘no’ and ‘not’ based on their distribution in clause found in The Jakarta Post June 2013; and (3) What is the funct ion of negative markers ‘no’ and ‘not’ based on the scope and focus of the sentences found in The Jakarta Post June 2013.The method used in this research is qualitative approach and content or document analysis as the type of study. The data of this research were the sentences containing negative markers of ‘no’ and ‘not’ taken from the 4 articles of The Jakarta Post June 2013 which discussed the political issues. The writer took 4 articles based on their variety of negat ive markers of ‘no’ and ‘not’ in their distribution in phrase and clause.The result of this research shows that there were seven categories of negative marker ‘not’ based on its distribution in phrase. Four of them were discovered in the objects, and there were five categories of negat ive marker ‘no’ based on its distribution in phrase,  in which only one of them discovered in the objects. Meanwhile, there were three categories of negat ive markers ‘no’ and ‘not’ based on their distribution in clause,  in which all of them are discovered in the objects.On the other hand, the function of negative markers based on scope and focus gave variety to their meaning.The writer suggests the next researchers who want to do further research of this topic use other theories or the other negative markers in English. The next researcher can also conduct a research on the negation in its syntactic feature or semantic feature, or elaborate it with another field of study such as the morphological features to make their study more complete.